2020
DOI: 10.1108/hff-03-2020-0149
|View full text |Cite
|
Sign up to set email alerts
|

Radiative hybrid nanofluid flow past a rotating permeable stretching/shrinking sheet

Abstract: Purpose This paper aims to discuss a stability analysis on Cu-Al2O3/water nanofluid having a radiation and suction impacts over a rotating stretching/shrinking sheet. Design/methodology/approach The partial differential equations are converted into nonlinear ordinary differential equations usi… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
5

Citation Types

6
51
0

Year Published

2020
2020
2023
2023

Publication Types

Select...
8

Relationship

2
6

Authors

Journals

citations
Cited by 36 publications
(57 citation statements)
references
References 45 publications
6
51
0
Order By: Relevance
“…They concluded that, as the rotational and radiation parameters increase, the temperature profile increases as well. After that, Anuar et al, [36] discussed a three-dimensional steady rotating and radiative flow across a stretching/shrinking surface involving hybrid nanofluid. They observed that the range of dual solutions was reduced as the value of the rotational parameter increases.…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation
“…They concluded that, as the rotational and radiation parameters increase, the temperature profile increases as well. After that, Anuar et al, [36] discussed a three-dimensional steady rotating and radiative flow across a stretching/shrinking surface involving hybrid nanofluid. They observed that the range of dual solutions was reduced as the value of the rotational parameter increases.…”
Section: Introductionmentioning
confidence: 99%
“…From the literature review on preceding studies, it is crucial to consider such a problem as three-dimensional flow as this setting allows more comprehensive and realistic applications in the real-world. Anuar et al, [36] have considered a three-dimensional hybrid nanofluid flow over rotating stretching/shrinking sheet with the effect of radiation but without paying the attention to the influence of MHD and Joule heating. Therefore, this current study extended the work of Anuar et al, [36] by including the effect of MHD and Joule heating via Tiwari-Das model (see Tiwari and Das [56]).…”
Section: Introductionmentioning
confidence: 99%
“…Waini et al [16] also reported that the presence of a huge volume fraction of copper intensifies the skin friction coefficient and the local Nusselt number. Many other recent interesting investigations towards hybrid nanofluid, focusing on alumina and copper as the hybrid nanoparticles, with various configurations of parameters, have also been revealed by Yashkun et al [17], Lund et al [18,19], Aladdin et al [20], Roşca et al [21], Khashi'ie et al [22][23][24][25], Roy and Pop [26], Zainal et al [27], Anuar et al [28], Gangadhar et al [29] and Wahid et al [30].…”
Section: Introductionmentioning
confidence: 87%
“…This new kind of fluid, however, provides a great advance in heat conductivity, as proved by the work of Madhesh and Kalaiselvam [37], Tahat and Benim [38] and Devi and Devi [39]. A few researchers have undertaken mathematical investigations of the boundary layer flow of hybrid nanofluids on various surfaces such as in stretching/shrinking sheet [40][41][42], thin needle [43], curved surface [44] and Riga plate [45]. Ghadikolaei et al [46] studied the behavior of a hybrid nanofluid (Cu-Al 2 O 3 ) in a micropolar dusty fluid.…”
Section: Introductionmentioning
confidence: 99%
“…In addition, this study also comprises a novel attempt to discover the shrinking features of a dusty hybrid nanofluid. The existence of nonunique solutions is acknowledged in the literature [25,27,28,40,42,49]; hence, this paper focuses on obtaining a nonunique solution as well as performing a stability analysis thereof. It is expected that these findings will help engineers and researchers to understand the heat transfer mechanism in dusty hybrid nanofluids.…”
Section: Introductionmentioning
confidence: 99%